ANALISIS PEMETAAN KESUKAAN KONSUMEN (CONSUMER’S PREFERENCE MAPPING) TERHADAP ATRIBUT SENSORI PRODUK SOYGURT DIKALANGAN MAHASISWA FAKULTAS PERTANIAN UNIVERSITAS RIAU - Ilham Apandi; Fajar Restuhadi; Yusmarini ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Currently product soyghurt not as popular as yoghurt which first appeared in the middle of society and the market. This is possible because of differences in sensory characteristics soyghurt products that are less favored by consumers . In addition to , there is still a lack of effort in developing products manufacturer soyghurt direction preferred by konsumers.This study was conducted to determine the position of the sensory attributes of the seven types of products of yoghurt and soyghurt from the consumer preference. This research was carried out by using the internal and external preference mapping technique. The object of this research, were 7 types of samples from different products, which consists 3 types of products soygurt and 4 types of commercial yoghurt. Sensory analysis was performed hedonic test and descriptive test. Results of cluster analysis of hedonic test and principal component analysis of descriptive test were then analyzed using the technique of preference mapping. Sensory attributes choosen by the consumer in this study is a sweet taste, cheese aroma and smoothness and attributes that are most unpreferred by consumers is a sour taste and a strong smell of acid and followed by a bitter taste. Keywords: Consumers preference, preference mapping, sensory attribute, soygurt, yoghurt.